Increase of the transmission and emittance acceptance through a cyclotron‐based proton therapy gantry. Issue 4 (14th February 2022) - Maradia, Vivek; Giovannelli, Anna Chiara; Meer, David; Weber, Damien Charles; Lomax, Antony John; Schippers, Jacobus Maarten; Psoroulas, Serena
Abstract: Purpose: In proton therapy, the gantry, as the final part of the beamline, has a major effect on beam intensity and beam size at the isocenter. Most of the conventional beam optics of cyclotron‐based proton gantries have been designed with an imaging factor between 1 and 2 from the coupling point (CP) at the gantry entrance to the isocenter (patient location) meaning that to achieve a clinically desirable (small) beam size at isocenter, a small beam size is also required at the CP. Here we will show that such imaging factors are limiting the emittance which can be transported through the gantry. We, therefore, propose the use of large beam size and low divergence beam at the CP along with an imaging factor of 0.5 (2:1) in a new design of gantry beam optics to achieve substantial improvements in transmission and thus increase beam intensity at the isocenter. Methods: The beam optics of our gantry have been re‐designed to transport higher emittance without the need of any mechanical modifications to the gantry beamline. The beam optics has been designed using TRANSPORT, with the resulting transmissions being calculated using Monte Carlo simulations (BDSIM code). Finally, the new beam optics have been tested with measurements performed on our Gantry 2 at PSI. Results: With the new beam optics, we could maximize transmission through the gantry for a fixed emittance value. Additionally, we could transport almost four times higher emittance through the gantry compared to conventional optics, whilst achieving good transmissions through the gantry (>50%) with no increased losses in the gantry. As such, the overall transmission (cyclotron to isocenter) can be increased by almost a factor of 6 for low energies. Additionally, the point‐to‐point imaging inherent to the optics allows adjustment of the beam size at the isocenter by simply changing the beam size at the CP. Conclusion: We have developed a new gantry beam optics which, by selecting a large beam size and low divergence at the gantry entrance and using an imaging factor of 0.5 (2:1), increases the emittance acceptance of the gantry, leading to a substantial increase in beam intensity at low energies. We expect that this approach could easily be adapted for most types of existing gantries.